Assessment Practices and Assessment Skills of Teachers at Secondary School Level: Factorability and Associative Perspective - Eman Tariq; Awaiz Asif; Dr. Fariha Gul (Journal of Peace, Development and Communication, 2023)
Assessment skills are an essential part of the assessment in the classroom for effective learning. These skills influence on practices of teachers for classroom assessment. This study seeks to evaluate the perceived competence and assessment practices of secondary school teachers regarding assessment. Quantitative research was employed to gather data from the participants. The sample was selected through multistage sampling, where at the first stage, schools were chosen through ratio sampling and at a later stage, the teachers from each school were selected through convenient sampling. Only hundred (N=100) teacher at the secondary school level were selected from public and private schools. The data was collected by visiting the schools through survey questionnaire. The data was analyzed using inferential statistics, including association between variables and mean differences. The results indicate a positive relationship between assessment skills and assessment practices. The study concluded that teachers should know about assessment skills and assessment practices to evaluate the students learning in the classroom for better academic results. It is recommended that school directors should arrange a training workshop for the teachers to increase their knowledge and skills in assessment practices in the classroom.